Energy analysis of spherical and Berkovich indentation contact damage in commercial polycrystalline silicon carbide. Issue 1 (January 2017) - Datye, Amit; Lin, Hua-Tay
Abstract: This research aims at enhancing the understanding of the role of processing and microstructure on the deformation of and fracture of polycrystalline silicon carbide based ceramics when subjected to blunt (spherical) and sharp (pyramidal) indenters. The role of microstructure and material properties on the energy absorption capability of SiC is studied. By examining the behavior of several SiC materials during nanoindentation experiments using spherical and pyramidal indenters, it is possible to make predictions about methods to improve the ductility and fracture toughness of SiC to optimize its energy absorption. The applicability of the area under the irreversible part of the indentation load displacement curve (energy dissipated during loading) to predict the performance of SiC under contact loading is examined. Results from experimental data show that the polycrystalline SiC material properties like hardness and modulus are relatively insensitive to the amount of indentation damage when the indent size is more than the average grain size. It can also be concluded that during pyramidal indentation for the polycrystalline samples analyzed, grain-size plays a much more important role in energy dissipation than the grain boundary phases or any other indentation damage relate effects.